Materials Imaging and Dynamics (MID) instrument at the European X‐ray Free‐Electron Laser Facility. (15th February 2021) - Madsen, A.; Hallmann, J.; Ansaldi, G.; Roth, T.; Lu, W.; Kim, C.; Boesenberg, U.; Zozulya, A.; Möller, J.; Shayduk, R.; Scholz, M.; Bartmann, A.; et al.
Abstract : The Materials Imaging and Dynamics (MID) instrument at the European X‐ray Free‐Electron Laser facility is described. Recent commissioning results are discussed to illustrate the potential experimental applications of MID. Abstract : The Materials Imaging and Dynamics (MID) instrument at the European X‐ray Free‐Electron Laser (EuXFEL) facility is described. EuXFEL is the first hard X‐ray free‐electron laser operating in the MHz repetition range which provides novel science opportunities. The aim of MID is to enable studies of nano‐structured materials, liquids, and soft‐ and hard‐condensed matter using the bright X‐ray beams generated by EuXFEL. Particular emphasis is on studies of structure and dynamics in materials by coherent scattering and imaging using hard X‐rays. Commission of MID started at the end of 2018 and first experiments were performed in 2019.